Neonatal Cerebral Sinovenous Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Universities of Toronto and Calgary, Canada performed a retrospective case-control study of infants with neonatal cerebral sinovenous thrombosis (CSVT) recruited in the SickKids Children's Stroke Program, Jan 1992-Dec 2006.